2020
DOI: 10.2176/nmc.oa.2020-0047
|View full text |Cite
|
Sign up to set email alerts
|

Diagnosis and Operative Management of Carotid Endarterectomy in Patients with Twisted Carotid Bifurcation

Abstract: Although carotid endarterectomy (CEA) is an established procedure, technical modifications are required when anatomical features are unusual. The present study aimed to determine the characteristics of diagnostic features, surgical management, and outcomes of patients with a twisted carotid bifurcation (TCB). We assessed 108 consecutive patients by cervical carotid echography (CCE) and black-blood magnetic resonance imaging (BB-MRI) before they underwent 115 CEA procedures. We classified carotid bifurcation (C… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
16
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
6
2

Relationship

2
6

Authors

Journals

citations
Cited by 13 publications
(16 citation statements)
references
References 17 publications
0
16
0
Order By: Relevance
“…We have reported details of the surgical maneuver for CEA in other articles. 21 , 22) In terms of using an internal shunt, if SSEP or SSEP+MEP showed a significant change at the time of clamping of the distal ICA, we initially asked the anesthesiologist to elevate systolic ABP up to 20–30% of the preoperative ABP. If the neuromonitor remained unimproved despite this increase in BP, we inserted the internal shunt immediately.…”
Section: Methodsmentioning
confidence: 99%
“…We have reported details of the surgical maneuver for CEA in other articles. 21 , 22) In terms of using an internal shunt, if SSEP or SSEP+MEP showed a significant change at the time of clamping of the distal ICA, we initially asked the anesthesiologist to elevate systolic ABP up to 20–30% of the preoperative ABP. If the neuromonitor remained unimproved despite this increase in BP, we inserted the internal shunt immediately.…”
Section: Methodsmentioning
confidence: 99%
“…This anomaly is called as lateral ECA, lateral position of ECA, or twisted carotid bifurcation. 2) Furthermore, the right carotid artery extended medial to the right greater horn of HB and the SHTC. Carotid artery stenting (CAS) was also considered, but the calcification was so severe in the entire circumference that CAS would be extremely difficult.…”
Section: Case Presentationmentioning
confidence: 98%
“…One advantage of head rotation ≥45° is the possibility of dissecting the internal carotid artery (ICA) more distally or accessing a twisted carotid bifurcation. 10 , 11) For expansion of the distal ICA, Takigawa et al used a radiolucent head frame to extend the patient’s neck. 12) In any case, the surgeon takes the head and neck position to expose the distal ICA for safe CEA ( Fig.…”
Section: Positioning For Ceamentioning
confidence: 99%
“…3B ). 11 , 13) Kazimierczak et al 14) reported a randomized study of camouflage (transverse) incision versus longitudinal incision. Although no significant difference in mortality or morbidity was seen between groups, scar assessment scale score was significantly better in patients with camouflage incision than in patients with longitudinal incision.…”
Section: Skin Incisionmentioning
confidence: 99%
See 1 more Smart Citation